Getting to know you: Identification of pygmy killer whales (Feresa attenuata) and melon-headed whales (Peponocephala electra) under challenging conditions - Siciliano,Salvatore; Brownell Jr.,Robert L. (Universidade de São Paulo, Instituto Oceanográfico, 2015)
Abstract Melon-headed whale (Peponocephala electra) and Pygmy killer whale (Feresa attenuata) are very poorly known species and are often confused with each other. We examined in detail Figure 3 in MARIGO and GIFFONI (2010) who reported that two melon-headed whales were taken in a surface driftnet about 90 nm off Santos, Brazil. We concluded they were in fact pygmy killer whales and explain our reasoning. To aid in future identifications, we illustrate and describe some of the main differences between these two species of small cetaceans. The incident reported by MARIGO and GIFFONI (2010) might represent the 'tip of the iceberg' regarding the incidental catches of cetaceans by pelagic drift nets off Brazil. Offshore driftnetting operating along the south-southeastern coast of Brazil may threaten pygmy killer whales.